Crisis in Lebanon: camps for Syrian refugees? - Loveless, J (Refugee Studies Centre, University of Oxford, 2013)
Lebanon has absorbed the enormous Syrian influx but at a high cost to both refugees and Lebanese populations. Current humanitarian programmes can no longer cope and new approaches are needed.